Técnicas activas y su contribución al aprendizaje de la matemática, en los estudiantes del séptimo grado de la escuela de Educación General Básica Teniente Hugo Ortiz, período académico 2018-2019. Lineamientos alternativos - Ojeda Ojeda, Jose Jairo (2019)
The investigation Active techniques and their contribution to the learning of mathematics, in the students of the seventh grade of the school of Basic General Education Teniente Hugo Ortiz, academic period 2018-2019. Alternative guidelines, has as a general objective to determine the active techniques and their contribution to the learning of Mathematics in the seventh grade students, parallel "A", of the above mentioned institution. The type of study is descriptive and its design quali-quantitative; the applied methods were: observational, descriptive, inductive, deductive, hermeneutic, scientific, analytical, synthetic and statistical; the techniques: observation and survey; the instruments: observation guide, checklist and questionnaire; and, the procedures: diagnosis, theoretical foundation and the design of the alternative guidelines; hence, in this last procedure was taken as a reference the diagnosis made in the teaching-learning process of Mathematics, in which, the problem detected is the monotonous-traditional application of certain techniques, which are the product of ignorance of another type of active procedures aimed at the training of students. The participating population was 64 students and two teachers from the seventh grade of General Basic Education, of which 32 students and a parallel teacher "A" were chosen for this research. The work is concluded confirming that the different active techniques, such as: demonstration, exercise, simulation, problem solving, learning tournament, mathematical puzzles, cedillas, butterfly, among others; contribute significantly to the teaching-learning process of the subject; since teachers and students carry out an active-participatory construction of knowledge, leaving behind the old currents of the traditional school.